AN OVERVIEW OF THE MAIN CHANGES IN THE RULES OF GOOD LABORATORY PRACTICE (THE ORDER FROM 01 APRIL 2016 № 199n ENTERED INSTEAD OF THE ORDER OF MINISTRY OF HEALTH OF 23 AUGUST 2010 №708n) - M. S. Zhuravleva; M. V. Lebedeva (Разработка и регистрация лекарственных средств)
This article provides an overview of the changes in requirements, processes, organization, planning, conducting and quality control of preclinical studies medicines, as well as making their results and archiving, approved by order of Ministry of Health of the Russian Federation from 01 April 2016 N 199n.